ANALISIS KEPUTUSAN GENERASI Z DALAM MEMILIH BANK DIGITAL: PRESPEKTIF TEORI DIFFUSION OF INNOVATION - Aulia Rahmawati; Khaerunnisa Nur Fatimah Syahnur (AkMen JURNAL ILMIAH, 2023)
This research examines the factors that encourage someone to use a digital bank where the context of this research is generation Z in Makassar. The Diffusion of Innovation (DOI) theory is the umbrella theory used in this research which aims to provide a different perspective where most research related to digital banks uses the Technology Acceptance Model (TAM) Theory. A quantitative approach with a cross-sectional design to explore factors that can influence a person's acceptance of using a Digital Bank. The sample in this research is generation Z who live in Makassar City. Data collection was carried out using an online questionnaire via Google Form with a total of 106 sample respondents. Data analysis uses Structural Equation Modeling (SEM) techniques with SmartPLS 3.0. This research found that perceived compatibility and perceived complexity have no influence on Generation Z's desire to adopt Digital Bank technology. On the other hand, perceptions of relative advantage and self-efficacy towards technology have a significant influence on their willingness to adopt technology in the Digital Bank context. Generation Z is a potential market for Digital Banks. It is important to study the decision to use a digital bank in more depth. This research provides input regarding factors that influence Generation Z's attitudes and interest in adopting technology from Digital Banks which have not been specifically researched.